2013
DOI: 10.1016/j.spinee.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Injection of human umbilical tissue–derived cells into the nucleus pulposus alters the course of intervertebral disc degeneration in vivo

Abstract: Background context Patients often present to spine clinic with evidence of intervertebral disc degeneration (IDD). If conservative management fails, a safe and effective injection directly into the disc might be preferable to the risks and morbidity of surgery. Purpose To determine whether injecting human umbilical tissue–derived cells (hUTC) into the nucleus pulposus (NP) might improve the course of IDD. Design Prospective, randomized, blinded placebo–controlled in vivo study. Patient sample Skeletally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 50 publications
0
53
0
1
Order By: Relevance
“…An alternative approach is the co-culture of IVD cells with MSCs in the 'one-surface system' (also known as direct co-culture or contact system), three-dimensional systems (alginate beads) and culture of two cell lines separated by a porous membrane (also termed insert system, indirect co-culture or non-contact system) (19). Injection of MSCs into the disc space was also assayed (16,20).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is the co-culture of IVD cells with MSCs in the 'one-surface system' (also known as direct co-culture or contact system), three-dimensional systems (alginate beads) and culture of two cell lines separated by a porous membrane (also termed insert system, indirect co-culture or non-contact system) (19). Injection of MSCs into the disc space was also assayed (16,20).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous stem cell types have been used in the field of cell transplantation for the treatment of IDD, such as bone marrow-derived stem cells (BMSCs) (10), adipose-derived MSCs (ADMSCs) (11), human umbilical tissue-derived cells (12) and synovium-derived stem cells (13 (14,15). Certain studies have reported that these stem cells lack viability, proliferation and matrix biosynthesis under conditions resembling the IVD microenvironment, which negatively influences the biological and metabolic vitality of stem cells and impairs their repair potential (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Some have observed that UC-MSCs, compared with BM-MSCs, are characterized by superior extracellular matrix synthesis in terms of glycosaminoglycans (GAGs) and collagen I production, consistent with a "fibrocartilaginous" commitment, while BM-MSCs seem to be more prone to collagen II synthesis and, consequently, to show better chondrogenic differentiation (15). For these reasons, UC-MSCs seem to be good candidates for intervertebral disk regeneration, as shown in different studies (16,17). Even though this preclinical application may provide an intriguing solution to a major problem in the general population, we, on the other hand, still believe that UC-MSCs offer potential for cartilage regeneration.…”
Section: J Ointsmentioning
confidence: 79%